Orexin‐1 receptor signalling in the prelimbic cortex and ventral tegmental area regulates cue‐induced reinstatement of ethanol‐seeking in iP rats. (20th April 2015) - Brown, Robyn Mary; Kim, Andrezza K.; Khoo, Shaun Yon‐Seng; Kim, Jee Hyun; Jupp, Bianca; Lawrence, Andrew John
Abstract: Orexins (hypocretins) are hypothalamic neuropeptides that innervate the entire neuraxis, including the prelimbic cortex and ventral tegmental area and have been implicated in ethanol‐seeking behaviour. The present study aimed to use the orexin‐1 (OX1 ) receptor antagonist SB‐334867 to examine the role of prelimbic cortex and ventral tegmental area OX1 receptors in cue‐induced reinstatement of ethanol‐seeking. Ethanol‐preferring rats (iP) rats were trained to self‐administer ethanol (10 percent v/v, FR3) or sucrose (0.2–1 percent w/v, FR3) in the presence of reward‐associated cues before being implanted with indwelling guide cannulae. Rats then underwent extinction training for 11 days. On test days, rats were given a microinjection of vehicle or SB‐334867 (3 μg/side) and presented with reward‐associated cues to precipitate reinstatement. Results show SB‐334867 infused into the prelimbic cortex attenuated cue‐induced reinstatement of ethanol‐seeking, but not sucrose‐seeking. OX1 antagonism in the ventral tegmental area also attenuated cue‐induced reinstatement of ethanol‐seeking. These findings suggest that OX1 receptors located in the prelimbic cortex and ventral tegmental area are part of a circuit driving cue‐mediated ethanol‐seeking behaviour. Abstract : We used the orexin‐1 (OX1 ) receptor antagonist SB‐334867 to examine the role of prelimbic cortex and ventral tegmental area OX1 receptors in cue‐induced reinstatement of ethanol‐seeking. SB‐334867 infused into the prelimbic cortex attenuated cue‐induced reinstatement of ethanol‐seeking, but not sucrose‐seeking. OX1 antagonism in the ventral tegmental area also attenuated cue‐induced reinstatement of ethanol‐seeking. These findings suggest that OX1 receptors located in the prelimbic cortex and ventral tegmental area are part of a circuit driving cue‐mediated ethanol‐seeking behavior.